Predstavitev prekmurskih rokopisnih pridig iz 1. polovice 20. stoletja - Horvat, Nina (Slavia Centralis, 2020)
PRESENTATION OF PREKMURJE MANUSCRIPT SERMONS FROM THE FIRST HALF OF THE 20TH CENTURYThe article presents the handwritten sermons of Prekmurje, which were found a few years ago in the Parish of Martjanci at the relative of the deceased parish priest Andrej Berden. These are Catholic sermons written for Sundays and religious holidays. There are more than five hundred in all; they were written by different authors from the turn of the 20th century to approximately the 1930s in various parishes of Prekmurje – most of them from the Parish of Črenšovci and Parish of Martjanci. The sermons complement the story of the development of the Prekmurje language in the Catholic Church, and their finding confirms that the church literature in Prekmurje deserves further research.
Keywords: Prekmurje manuscript sermons; Prekmurje language; Parish of Črenšovci; Parish of Martjanci; Jožef Horvat